2011
DOI: 10.1007/s00439-011-1051-4
|View full text |Cite
|
Sign up to set email alerts
|

Spread of X-chromosome inactivation into chromosome 15 is associated with Prader–Willi syndrome phenotype in a boy with a t(X;15)(p21.1;q11.2) translocation

Abstract: X-chromosome inactivation (XCI) is an essential mechanism in females that compensates for the genome imbalance between females and males. It is known that XCI can spread into an autosome of patients with X;autosome translocations. The subject was a 5-year-old boy with Prader-Willi syndrome (PWS)-like features including hypotonia, hypo-genitalism, hypo-pigmentation, and developmental delay. G-banding, fluorescent in situ hybridization, BrdU-incorporated replication, human androgen receptor gene locus assay, SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
5
15
0
Order By: Relevance
“…Recently, it has become possible to investigate genome-wide DNA methylation patterns using a method based on a CpG island microarray with sodium-bisulfite treated DNA [48] or with methylated DNA immunoprecipitation (MeDIP) [49]. In this study, we used an assay based on a CpG island microarray with sodium-bisulfite treated DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has become possible to investigate genome-wide DNA methylation patterns using a method based on a CpG island microarray with sodium-bisulfite treated DNA [48] or with methylated DNA immunoprecipitation (MeDIP) [49]. In this study, we used an assay based on a CpG island microarray with sodium-bisulfite treated DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Sharp et al also found that genes could still be silenced in the autosome even though there is no spreading of late replication [Sharp et al, ], suggesting that late‐replication study is not good enough to determine the spreading of X inactivation. Recently, Sakazume et al studied the DNA methylation changes on a case with X;15 translocation using DNA immunoprecipation with microarray and observed that there was gain in DNA methylation along the translocated autosome [Sakazume et al, ]. In this report, we also investigated into the spreading of X inactivation by studying DNA methylation in a baby with an unbalanced X;15 translocation using a whole genome DNA methylation microarray.…”
Section: Introductionmentioning
confidence: 89%
“…Methylation spread across biparental origins was manifested in patients with Prader–Willi syndrome-like features displaying hypo-pigmentation symptoms. The maternal X-chromosome was not only inactivated by methylation, but its aberrant methylation was also furthered into the paternal chromosome 15 leading to the abnormal hypermethylation and silencing of downstream targets SNRPN and OCA2 [37]. Similarly, selective “seed” methylation occurring at the large tandem repeats becomes important for the subsequent extension of the critically methylated region that resulted in stable silencing of a locus namely FWA and thus prevented late flowering in Arabidopsis thaliana [38].…”
Section: Discussionmentioning
confidence: 99%